Cellular distribution and interaction between extended renin-angiotensin-aldosterone system pathways in atheroma. (August 2017) - Nehme, Ali; Zibara, Kazem
Abstract: The importance of the renin-angiotensin-aldosterone system (RAAS) in the development of atherosclerotic has been experimentally documented. In fact, RAAS components have been shown to be locally expressed in the arterial wall and to be differentially regulated during atherosclerotic lesion progression. RAAS transcripts and proteins were shown to be differentially expressed and to interact in the 3 main cells of atheroma: endothelial cells, vascular smooth muscle cells, and macrophages. This review describes the local expression and cellular distribution of extended RAAS components in the arterial wall and their differential regulation during atherosclerotic lesion development. Highlights: All angiotensin peptides could be produced in atheroma. Final effects of RAAS in atheroma depend on the combination of expressed receptors. Mutual regulations exist between different RAAS pathways in atheroma. VSMCs are the major participants in the generation of all angiotensin peptides. RAAS should be globally studied so that misleading conclusions could be avoided.